FEMINISM IN PATRIARCHAL SOCIETY REFLECTED IN THE MAIN CHARACTER OF PEREMPUAN BERKALUNG SORBAN MOVIE - Farida Hannum Siagian; I Wy Dirgeyasa; Indra Hartoyo (LINGUISTICA, 2018)
This study is aimed to analyze what the feminism varieties and how is the feminism in patriarchal reflected by main character Annisa in Perempuan Berkalung Sorban movie. This study is conducted with the descriptive qualitative method. The source of the data of the analysis is Perempuan Berkalung Sorban movie and the data are linguistic feature that are format as sentence by the main character. The data were collected by the documentary technique and the instrument is documentary sheets. The study results that (1) The main character reflected the feminism varieties. Based on the Feminist Thought book there are three varieties of feminism. Liberal feminism, Radical feminism and Socialist Marxists feminism. The main character reflected the three kinds of feminism such as Liberal Feminism, Radical feminism, Socialist Marxist Feminism. The main character Annisa is reflected most dominant appeared Radical feminism. Annisa is powerful and rebellious women. She wants to get the equal with the man without any discrimination gender. (2) The feminism in patriarchal society in reflected is Annisa to represent the women movement to against all of objection toward woman. The each utterances of Annisa represent she is against all forms of women discrimination in private patriarchy and public patriarchy. The research focuses on the analysis of feminism in patriarchal society in the main character can be interpreted through Annisa as a main character and sentences of the movie and it is found of the main character reflected the feminism in a patriarchal society.Keywords:feminism, varieties, patriarchal, main character, movie.